2009
DOI: 10.1099/vir.0.011791-0
|View full text |Cite
|
Sign up to set email alerts
|

Bovine leukemia virus can be classified into seven genotypes: evidence for the existence of two novel clades

Abstract: Previous studies have classified the env sequences of bovine leukemia virus (BLV) provirus from different locations worldwide into between two and four genetic groupings. These different studies gave unique names to the identified groups and no study has yet integrated all the available sequences. Thus, we hypothesized that many of the different groups previously identified actually correspond to a limited group of genotypes that are unevenly distributed worldwide. To examine this hypothesis, we sequenced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
84
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 79 publications
13
84
0
2
Order By: Relevance
“…In recent years, several authors have tried to classify BLV strains into groups, clusters, or genotypes [8,11,23,33]. Initial phylogenetic analysis conducted with a 519-nt fragment of the BLV env gp51-encoding gene of 32 foreign and six domestic BLVs resolved all of the previously identified genotypes and clustered all Croatian sequences in a separate clade, revealing a new genotype.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In recent years, several authors have tried to classify BLV strains into groups, clusters, or genotypes [8,11,23,33]. Initial phylogenetic analysis conducted with a 519-nt fragment of the BLV env gp51-encoding gene of 32 foreign and six domestic BLVs resolved all of the previously identified genotypes and clustered all Croatian sequences in a separate clade, revealing a new genotype.…”
Section: Discussionmentioning
confidence: 98%
“…Up to seven BLV genotypes can be identified by RFLP analysis [1,10,20]. A recent phylogenetic study on the BLV env gene of strains from different parts of the world has allowed these viruses to be classified into seven genotypes [27,33]. More recently, a [24] has indicated that BLV can be classified into at least eight genotypes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Argentine (Dube et al 2000;Licursi et al 2003;Monti et al 2005;Dube et al 2009;Rodriguez et al 2009), genotype-1,…”
Section: G E O G R a P H I C A L D I S T R I B U T I O N O F B L V Gementioning
confidence: 99%
“…Compartilhando arranjo estrutural e genético com os deltaretrovírus humanos 2 , associados a leucemia de células T e linfoma em adultos, ambos desenvolvem doença crônica e proliferação das células-alvo envolvendo células e mediadores imunitários. No mundo, apenas alguns países conseguiram sua erradicação 3 . No Brasil, todavia, sua ocorrência vem sendo relatada em quase todos os Estados 4 .…”
Section: Introductionunclassified